Nivel de conocimiento y practicas de las enfermeras sobre aspiración de secreciones en pacientes con intubación endotraqueal Hospital Nacional Almanzor Aguinaga Asenjo - Chiclayo - Tuñoque Coronado, Sonia Elizabeth (2016)
La This research was conducted in order to determine the level of knowledge and practices that have nurses on suctioning in patients with endotracheal intubation in shock trauma unit emergency service of Almanzor Aguinaga Asenjo National Hospital October - December 2014. quantitative, descriptive and cross-sectional research, the sample population was 30 nurses (as), who were applied a survey to obtain the level of knowledge and an Observation on suctioning; considering at all times the ethical principles. Data were processed using Microsoft Excel 2010. The results are presented in Tables of double entrance, coming to the following conclusions: The 56.66% of the nurses in the shock trauma unit have a very good knowledge of suctioning in patients with endotracheal intubation, the 43.33% regular knowledge; no low level of knowledge was obtained. As for what nurses know, they are: evaluation of the patient prior to the procedure, complications and contraindications for suctioning .. As for the practice undertaken by nurses, it was found that 80% of nurses do a good practice in the art of suctioning, 20% poor practice. As observed in the three stages was obtained before suctioning 85.71% are in the categorization of good, poor 14.29%; during practice good 71.43%, 28.57% and poor practice after the 77.77% and 22.22% good in poor practice. Of the total 66.67% nurses studied fluidized no secretions and 43.33% do not place the patient in semifowler position at the time of aspiration.